Zur Nähe von Denken und Dichten beim frühen Heidegger. Eine Spurensuche - Holger Zaborowski (Phainomena, 2022)
On Proximity of Thinking and Poetizing in Early Heidegger. A Search for Traces --- The paper discusses the question of the role of the relationship between thinking and poetizing, which is of immense importance for Heidegger’s late work, in his early hermeneutics of facticity. Heidegger’s early thinking is denoted with the search for the unconditionality of factical life in its historicity that cannot be comprehended neither under the conditions of a worldview nor of a strict science in Husserl’s sense. In his search, he continually encounters the realms of art and poetry, which he experiences as fundamental points of orientation. Although Heidegger does not expressly reflect upon them, such experiences of the proximity of thinking and poetizing did leave traces in his lectures.